2007
DOI: 10.1038/sj.bmt.1705677
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of bacteremia and factors associated with multi-drug-resistant gram-negative bacteremia in hematopoietic stem cell transplant recipients

Abstract: The incidence of Gram-negative bacteremia has increased in hematopoietic stem cell transplant (HSCT) recipients. We prospectively collected data from 13 Brazilian HSCT centers to characterize the epidemiology of bacteremia occurring early post transplant, and to identify factors associated with infection due to multi-drug-resistant (MDR) Gram-negative isolates. MDR was defined as an isolate with resistance to at least two of the following: third-or fourth-generation cephalosporins, carbapenems or piperacillin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
88
0
11

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(112 citation statements)
references
References 29 publications
13
88
0
11
Order By: Relevance
“…27 Gram-positive organisms, especially CNS, were the most frequent etiology of BSI in both periods, in agreement with other studies involving HSCT recipients. 3,5,10,28 The frequency of Gram negatives was similar in both groups, as was the rate of multidrug resistance among them. The overall rate of multidrug-resistant Gram-negative bacilli was 21%.…”
Section: Discussionmentioning
confidence: 80%
“…27 Gram-positive organisms, especially CNS, were the most frequent etiology of BSI in both periods, in agreement with other studies involving HSCT recipients. 3,5,10,28 The frequency of Gram negatives was similar in both groups, as was the rate of multidrug resistance among them. The overall rate of multidrug-resistant Gram-negative bacilli was 21%.…”
Section: Discussionmentioning
confidence: 80%
“…Only 1 extended-spectrum β-lactamaseproducing organism was identified in our study, whereas rates as high as 25% to 44% have been observed in allogeneic HSCT recipients at other centers. 12,21 In comparing our study data with our institutional antibiogram, we note that the rate of fluoroquinolone-resistant organisms is considerably higher in our allogeneic HSCT recipients than in our general patient population, reflecting not only their higher antimicrobial exposures but perhaps also their more extensive exposure to the inpatient hospital setting. Therefore, institutional antibiograms that are compiled from all pooled patient groups may not be as useful in guiding empiric antibiotic selection in those who undergo allogeneic HSCT and other patient groups with heavy antibiotic exposures.…”
Section: Discussionmentioning
confidence: 88%
“…Another finding that showed a predominance of Gram-negative BSIs in the current study was consistent with those reported by some institutions in Taiwan, 57,58 but in contrast to numerous studies that have found a predominance of Gram-positive bacteria. [1][2][3][4][5]40,55,59 Literature from other countries in general showed a trend shifting from GNB predominance to Gram-positive bacteria predominance. 3,[60][61][62][63] Changing trends of nosocomial BSIs pathogens over time, variations among institutional or geographic epidemiology of nosocomial BSIs, and variations of prophylactic antibiotics applied may account for this discrepancy.…”
Section: Discussionmentioning
confidence: 99%